Young Widows and Life Strategies Amid Social Stigma - Awaru, A. Octamaya Tenri (Universitas Tanjungpura, 2025)
Changes in family structure due to divorce have created social and economic challenges for young women who must live as widows in a patriarchal society. This study is important because few studies have specifically examined the survival strategies of young widows in rural Indonesia, particularly in Sinjai Regency, where divorce rates are relatively high. The research employs a qualitative descriptive method with a case study approach involving 11 women aged 18–30 who filed for divorce at the Sinjai Religious Court, selected through purposive sampling. The findings reveal four main strategies: (1) active (working, entrepreneurship, and using digital technology), (2) passive (living frugally and depending on family), (3) network (mobilizing social and community support), and (4) self-development (attending training, continuing education, and improving skills). These strategies reflect women’s agency in negotiating structural constraints and reconstructing their social identity after divorce.Theoretically, this study enriches the sociology of family and gender by illustrating adaptive rationality among divorced young women. Practically, the findings can serve as a basis for family- and community-based empowerment programs to strengthen the economic independence and social resilience of young widows.